2016
DOI: 10.1039/c5tb01994j
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated gold nanoparticle libraries for label-free multiplexed lectin biosensing

Abstract: Glycosylated nanoparticle libraries are developed to enable ‘barcode’ sensing of lectins and toxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 45 publications
1
50
0
1
Order By: Relevance
“…This is in line with the inhibitory data showing that 75% galactose was the most potent in terms of EC 50 and total inhibition achieved. This rational for optimal binding agrees with previous reports that ~30% mannose is optimal for glyconanoparticles agglutinating RCA 120 . These observations could support an additional binding mode for mannose, and that binding is not only due to the galactose ligands.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with the inhibitory data showing that 75% galactose was the most potent in terms of EC 50 and total inhibition achieved. This rational for optimal binding agrees with previous reports that ~30% mannose is optimal for glyconanoparticles agglutinating RCA 120 . These observations could support an additional binding mode for mannose, and that binding is not only due to the galactose ligands.…”
Section: Resultssupporting
confidence: 91%
“…Multivalency is also observed to result in altered binding affinities compared to monovalent systems. Richards et al have reported that mannosylated gold nanoparticles have affinity toward RCA 120 , despite the monosaccharides having little or no affinity . Sequence‐controlled glycooligomers have shown increased affinity due to the nonbinding glycan providing steric shielding rather than more binding and mixed‐carbohydrate particles have been shown to have increased cell uptake into macrophages over the homogeneous equivalents .…”
Section: Introductionmentioning
confidence: 91%
“…Lectins have been used in targeted capture using novel approaches such as the self‐propelled microtubular nanoengines developed by Campuzano and others (), where microstructures conjugated to lectins autonomously “swim” in the solution to seek out and bind pathogens such as E. coli without the addition of exogenous labels. Although lectins have a low affinity relative to the other biorecognition agents discussed here, specificity can be significantly increased if multiplexing sensors are used to target pathogen‐associated molecular patterns rather than an individual cell surface target based on a single interaction between target and lectin (Richards and others ). Furthermore, lectins can be easily regenerated for repeated measurements and thus can be used as a regenerable biosensor in processing lines, food packaging, and so on.…”
Section: Comparison Of Current and Emerging Techniques For Monitoringmentioning
confidence: 99%
“…This works like a tongue – we only have five different tastes, but we are trained to use these to identify foods. We do the same, with a few sugars to identify pathogens [5–7]. …”
Section: Q You Recently Presented Work On a New ‘Chemical Tongue’ Appmentioning
confidence: 99%